Formation and preservation of an overstepped segmented lagoon complex on a high‐energy continental shelf. Issue 7 (28th June 2013) - Green, Andrew N.; Cooper, J. Andrew G.; Leuci, Rio; Thackeray, Zane; Mallinson, Dave
Abstract The duration of shoreline occupation at a given sea‐level, coastal response to sea‐level change and the controls on preservation of various shoreline elements can be recognized by detailed examination of submerged shorelines on the continental shelf. Using bathymetric and seismic observations, this article documents the evolution and preservation of an incised valley and lithified barrier complex between −65 m and −50 m mean sea‐level on a wave‐dominated continental shelf. The barrier complex is preserved as a series of aeolianite or beachrock ridges backed by laterally extensive back‐barrier sediments. The ridges include prograded cuspate lagoonal shoreline features similar to those found in contemporary lagoons. The incised valley trends shore‐parallel behind the barrier complex and records an early phase of valley filling, followed by a phase of extensive lagoonal sedimentation beyond the margins of the incised bedrock valley. Sea‐level stability at the outer barrier position (ca −65 m) enabled accumulation of a substantial coastal barrier that remained intact during a phase of subsequent slow sea‐level rise to −58 m when the lagoon formed. These lagoonal sediments are stripped seawards by bay ravinement processes which caused the formation of several prograded marginal cuspate features. An abrupt rise in sea‐level to −40 m, correlated with melt‐water pulse 1B, enabled the preservation of thick lagoonal sediments at the top of the incised valley fill and preservation on the sea bed of the cemented core of the barriers. This situation is unique to subtropical coastlines where early diagenesis is possible. The overlying sandy sediment from the uncemented upper portion of the barriers is dispersed by ravinement, partly burying the ridges and protecting the underlying sediments. The high degree of barrier or shoreline preservation is attributed to rapid overstepping of the shoreline, early cementation in favourable climatic conditions and the protection of the barrier cores by sand sheet draping.